Analysis of interaction between morphology and flow structure in a meandering macro-tidal estuary using 3-D hydrodynamic modeling. (5th January 2022) - Somsook, Kirana; Olap, Neriezza A.; Duka, Maurice A.; Veerapaga, Nagendram; Shintani, Tetsuya; Yokoyama, Katsuhide
Abstract: This study employs a 3-D numerical model to examine the behavior of primary and secondary flows on a macro-tidal estuarine bend with seasonally evolving morphology. Three scenarios were developed based on actual bathymetric surveys at the meander bend in the upper region of Japan's Chikugo macro-tidal estuary namely, S1: one month post-flood (channel at maximum capacity), S2: two months post-flood (onset of mud bar formation) and S3: nine months post-flood (most stable channel with low capacity). Secondary circulation begins before the center of the curve at −1/3.5 of the radius of curvature (θ), and fully develops between the center until +θ/3.5 for both flood and ebb phases. Primary flow mainly dominates the morphological evolution in the estuary, as secondary flow, which is responsible for the lateral transport of the sediments accounts for 10–15% of the primary flow. The residual currents for one tidal cycle are generally inwards, resulting in net lateral sediment transport near the bottom. Primary current decelerates due to the increase in cross-sectional area at the curve exit while secondary currents exhibit bottom inward flows at the curve center (S1). Since flood currents are larger than ebb due to tidal asymmetry, suspended sediments are transported landward, resulting in the mud bar formation inside the curve upstream (S2). Shear stress (τ) exceeds critical value of 1.8 N/m 2 especially at the inner bank during flood tide, but falls below this value during ebb. Since having τ greater than 1.8 N/m 2 causes large scouring, it is presumed that erosion, resuspension and transportation occur more actively during flood tide than ebb. The channel becomes more stable as its flow capacity decreases and together, the water flow is mainly directed towards the outer bank during the entire dry season due to further sedimentation at the inner bank (S3). The process is repeated until the occurrence of the next flood, hence giving insight on the seasonal variation in deposition and erosion in the estuarine curve. The overall flow structure and the trend of seasonal flow volume variation in the channel are similar along the streamline from entry to exit for both tidal phases. This study successfully establishes the roles of primary and secondary flows in the evolution of morphology in an actual macro-tidal estuarine setting with strong tidal asymmetry. Graphical abstract: Image 1 Highlights: Flow structure in seasonally evolving morphology was illustrated using 3-D flow model. Secondary circulation fully develops at the center of the curve. Water flow seasonally moves outwards due to sedimentation at inner bank. Flow structure and its seasonal change are similar for both flood and ebb phases.